The Contributions of Technology to Arabic Literature: Interactive Literature as a Model (The International Journal of Educational Sciences and Arts, 2026)
This study examines the contributions of technology to Arabic literature, taking interactive literature as a model for analyzing the transformations that have affected the structure of the literary text and the mechanisms of its production and reception in the digital age. It aims to clarify the concept of interactive literature and the terminological issues associated with it, as well as to identify its conditions, characteristics, and types, while tracing its beginnings in Arabic literature. The study also explores its artistic components and the extent to which the aesthetic function is realized through the electronic medium. Adopting a descriptive–analytical approach, the study concludes that interactive literature represents a qualitative shift in literary creativity, based on openness, multiplicity, and the active participation of the reader in constructing meaning, thereby transcending the limits of the traditional printed text.
Keywords: Interactive Literature; Technology; Digital Literature; Hypertext; Electronic Media